Brain Activity in Age-Related Macular Degeneration Patients From the Perspective of Regional Homogeneity: A Resting-State Functional Magnetic Resonance Imaging Study - Liu, Qi-Ying; Pan, Yi-Cong; Shu, Hui-Ye; Zhang, Li-Juan; Li, Qiu-Yu; Ge, Qian-Min; Shao, Yi; Zhou, Qiong (Frontiers in Aging Neuroscience, 2022)
Objective: In this study, the regional homogeneity (ReHo) method was used to investigate levels of cerebral homogeneity in individuals with age-related macular degeneration (AMD), with the aim of exploring whether these measures are associated with clinical characteristics. Materials and Methods: Patients with AMD and healthy controls attending the First Affiliated Hospital of Nanchang University were invited to participate. Resting state functional magnetic resonance images were recorded in each participant and levels of synchronous neural activity were evaluated using ReHo. Receiver operating characteristic (ROC) curves were used to evaluate the sensitivity and specificity of this method. Results: Eighteen patients with AMD (9 males and 9 females) and 15 healthy controls (HCS) were recruited. The two groups were approximately matched in age, gender and weight. Compared with controls, the ReHo values were significantly higher in the AMD group at the limbic lobe and parahippocampal gyrus, and were significantly reduced at the cingulate gyrus, superior frontal gyrus, middle frontal gyrus, inferior parietal lobule and precentral gyrus. Mean ReHo values at the cingulate gyrus and the superior frontal gyrus were negatively correlated with clinical symptoms. Conclusion: Brain neural homogeneity dysfunction is a manifestation of visual pathways in AMD patients, and may be one of the pathological mechanisms of chronic vision loss, anxiety and depression in AMD patients. In addition, the ReHo data may be useful for early screening for AMD. Keywords: age-related macular degeneration, neural regional homogeneity, resting state, functional magnetic resonance imaging